Iodine Accumulation and Tolerance in Sweet Basil (Ocimum basilicum L.) With Green or Purple Leaves Grown in Floating System Technique - Incrocci, Luca; Carmassi, Giulia; Maggini, Rita; Poli, Caterina; Saidov, Djamshed; Tamburini, Chiara; Kiferle, Claudia; Perata, Pierdomenico; Pardossi, Alberto (Frontiers in Plant Science, 2019)
Iodine deficiency is a serious world-wide public health problem, as it is responsible for mental retardation and other diseases. The use of iodine-biofortified vegetables represents a strategic alternative to iodine enriched salt for people with a low sodium diet. However, at high concentrations iodine can be toxic to plants. Therefore, research on plant iodine toxicity is fundamental for the development of appropriate biofortification protocols. In this work, we compared two cultivars of sweet basil (Ocimum basilicum L.) with different iodine tolerance: ‘Tigullio’, less tolerant, with green leaves, and ‘Red Rubin’, more tolerant and with purple leaves. Four greenhouse hydroponic experiments were conducted in spring and in summer with different concentrations of iodine in the nutrient solution (0.1, 10, 50, 100, and 200 M), supplied as potassium iodide (KI) or potassium iodate (KIO3). Plant growth was not affected either by 10 M KI or by 100 M KIO3, while KI concentrations higher than 50 M significantly reduced leaf area, total plant dry matter and plant height. The severity of symptoms increased with time depending on the cultivar and the form of iodine applied. Growth inhibition by toxic iodine concentrations was more severe in ‘Tigullio’ than in ‘Red Rubin’, and KI was much more phytotoxic than KIO3. Leaf iodine concentration increased with the iodine concentration in the nutrient solution in both varieties, while the total antioxidant power was generally higher in the purple variety. In both basil cultivars, a strong negative correlation was found between the photosynthesis and the leaf iodine content, with significant differences between the regression lines for ‘Tigullio’ and ‘Red Rubin’. In conclusion, the greater tolerance to iodine of the ‘Red Rubin’ variety was associated with the ability to withstand higher concentrations of iodine in leaf tissues, rather than to a reduced accumulation of this element in the leaves. The high phenolic content of ‘Red Rubin’ could contribute to the iodine tolerance of this purple cultivar.